2018
DOI: 10.1111/1462-2920.14396
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented microbial eukaryotes fuel the deep sea carbon pool in the tropical Western Pacific Ocean

Abstract: Phototrophic microbial eukaryotes dominate primary production over large oceanic regions. Due to their small sizes and slow sinking rates, it is assumed they contribute relatively little to the downward export of organic carbon via the biological pump. Therefore, the community structure of phototrophic cells in the deep ocean has long been overlooked and remains largely unknown. In this study, we used an integrative approach, including epifluorescence microscopy, sequencing of 18S rRNA and photosystem-II psbA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…The subtropical/tropical western Pacific Ocean is characterized by the relatively stable environmental conditions. Our measurements on surface water temperature, salinity, and inorganic nutrients were consistent with the ranges reported in previous studies (e.g., Gómez 2007;Wang et al 2019;Xu et al 2018;Zhao et al 2017), though with slight differences, which may be mainly due to the variations in sampling period. Nevertheless, the surface Chl a concentrations in the present study showed a wider range with the maxima higher than those reported in the previous studies in the same region, e.g., Zhao et al (2017), who recorded a range of 0.052-0.133 µg/L in the surface layer (vs. 0.009-0.204 µg/L in the present study).…”
Section: Environmental Characteristics Of the Sampling Sitessupporting
confidence: 91%
See 1 more Smart Citation
“…The subtropical/tropical western Pacific Ocean is characterized by the relatively stable environmental conditions. Our measurements on surface water temperature, salinity, and inorganic nutrients were consistent with the ranges reported in previous studies (e.g., Gómez 2007;Wang et al 2019;Xu et al 2018;Zhao et al 2017), though with slight differences, which may be mainly due to the variations in sampling period. Nevertheless, the surface Chl a concentrations in the present study showed a wider range with the maxima higher than those reported in the previous studies in the same region, e.g., Zhao et al (2017), who recorded a range of 0.052-0.133 µg/L in the surface layer (vs. 0.009-0.204 µg/L in the present study).…”
Section: Environmental Characteristics Of the Sampling Sitessupporting
confidence: 91%
“…The tropical/subtropical western Pacific Ocean is considered as oligotrophic and unproductive compared with the eastern Pacific and other oceans (Olson 2001). Several studies have been carried out on the spatial distributions of pico-and nanoplankton communities in this region (e.g., Liang et al 2016;Tsai et al 2005;Xu et al 2018). However, studies on the spatial distributions and diversity of planktonic ciliates have been scarce, and little is known about the factors that determine their distribution (Gómez 2007;Wang et al 2019;Zhao et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of López-García et al (2001) and Moon-van der Staay et al (2001), there has been a surge of studies on microbial eukaryotes diversity using sequencing based approaches from diverse marine environments, focusing more on the water columns than sediments (Edgcomb et al, 2002;Countway et al, 2007;Not et al, 2009;Scheckenbach et al, 2010;Pernice et al, 2015;Flegontova et al, 2016;Xu et al, 2018). Although…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we sequenced microbial eukaryotes based on total RNA extracts of samples from both MPs and SW in the Arctic Ocean. Using RNA instead of DNA extracts enabled us to target specifically the active assemblages, thus bypassing the bias from the dead/dormant cells, or extracellular DNA (Stoeck et al, 2007;Not et al, 2009;Orsi et al, 2013;Logares et al, 2014;Massana et al, 2015;Sun et al, 2016Sun et al, , 2017Sun et al, , 2019Sun et al, , 2020Xu et al, 2017Xu et al, , 2018Li et al, 2018). This study aimed to address the following questions: (1) do MPs and SW harbor distinct microbial eukaryotic communities and, if so, to what extent do they differ?…”
Section: Introductionmentioning
confidence: 99%